Mediating role of organizational partnership and hospital staff management in improving hospital performance and staff satisfaction - Mohammadi Yousefnejad , Seyedeh Nafiseh; Shokoh, Zahra; Madahian , Shiva; Firozabadi , Ameneh; Molaei , Hamidreza (Social Determinants of Health, 2023)
Background: The circumstances of employment are determined by a variety of elements in today's world. The present study investigated the mediating role of organizational partnership and hospital staff management in improving hospital performance and staff satisfaction. Methods: This study was applied, descriptive-correlation. The statistical population included all employees of hospitals in Bushehr province. Using stratified random sampling, 384 participants were chosen as the sample size based on Morgan's table. Organizational development was assessed using the 36-question questionnaire developed by Avolio, Gardner, and Valium, while organizational participation was assessed using the Hosseininoveh questionnaire. 30 elite individuals' opinions were sought after in order to verify and examine the face and content validity of the surveys. Over 0.70 indicates acceptable reliability, according to Cronbach's alpha coefficient. Data analysis tools included SPSS 23 and the Sobel test. Results: According to the findings, there is a link between organizational development in public organizations and internalized ethical perspective, idealized influence, and intellectual stimulation through organizational collaboration. Conclusion: Labor productivity is one of the most significant factors in economic policymaking. According to the studies and the trust of experts, one can expect productivity in other production factors when the factors affecting organizational development are first known.